Α-methyl-L-tryptophan: mechanisms for tracer localization of epileptogenic brain regions. (October 2011) - Chugani, Diane C
The purpose of this paper is to discuss the mechanisms of α-[ 11 C]methyl-L -tryptophan (AMT) PET as an in vivo biomarker for detection of epileptogenic cortex. AMT was originally designed as a tracer to measure the serotonin synthesis rate. This tracer was first applied in patients with medically refractory epilepsy in an attempt to detect changes in serotonin synthesis based upon reports of increased serotonergic innervation in cortical specimens obtained following epilepsy surgery. The first group of epilepsy patients undergoing AMT PET scans were patients with tuberous sclerosis complex. Studies of brain tissue subsequent to epilepsy surgery in these patients with tuberous sclerosis complex implicated the kynurenine pathway of tryptophan metabolism as a primary mechanism of increased brain tissue retention of AMT in epileptogenic brain regions, rather than alterations in serotonin synthesis. Kinetic analyses of AMT in brain tumors indicate changes in tryptophan transport and tissue retention in other pools as well. These studies indicate that AMT PET may be a biomarker of immune activation in the epileptogenic process.